Optimizing Sekar Handycraft Development Through Digitalization of MSMEs in Medan - Thamrin, Muhammad Husni; Harahap, Husnul Isa (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
MSMEs, especially the Handicraft sector have not been able to have a significant impact on the development of creative economy in Medan City. This condition is influenced by policy of imposing restrictions on community activities that have stopped economic activity. Thus, digitization of MSMEs becomes one way to increase sales of handicraft products. Furthermore, affected MSMEs of Sekar Handycraft need to be given digitalization training, in order to be able to develop in midst of the covid-19 pandemic. The purpose of the training activities, among others; First, assist in creation and management of Handycraft Sekar Website. Second, training how to photo products in the photo box studio and photo editing with various applications. Third, the development of social media management, such as; facebook, Instagram, youtube to expand the market of handicraft products from Sekar. Overall this training is carried out with participatory techniques, participants are actively involved in all stages of training activities. Outside the devotion recommends the Manager sekar Handycraft to conduct various digitization training and build partnerships to several MSMEs Handycraft in Medan City. Thus, construction and assistance of MSMEs Sekar Handycraft must be done in a sustainable manner.